Sarcomatoid carcinoma of the urinary bladder: A case report - Mallik, AU; Rahman, MZ; Sarker, MMR (Pulse, 2011)
Background: Sarcomatoid carcinoma of the urinary bladder is very rare variety of transitional cell carcinoma (TCC) with a prominent component of spindle-shaped cell. The incidence rate of this tumor is 0.5 % of all bladder tumors. Case report: Herein, we report a case of sarcomatoid carcinoma of urinary bladder of a farmer aged 70 years old, smoker with the complaints of lower abdominal pain, mild burning during urination and 3 episodes of painless gross haematuria. USG of KUB revealed a cystic lesion in front of the anterior bladder wall. We planned for total cystectomy but patient refused, so, partial cystectomy was carried out. Diagnosis was confirmed by histopathological study. Patient refused for radiotherapy or chemotherapy and died after 7 months of surgery due to metastasis. DOI: http://dx.doi.org/10.3329/pulse.v4i1.6961 Pulse Vol.4 January 2010 p.28-29